2014
DOI: 10.1371/journal.pone.0092834
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Deep-Water Coral Diversity in the Caribbean Basin and Adjacent Southern Waters: An Approach based on Records from the R/V Pillsbury Expeditions

Abstract: The diversity of deep-water corals in the Caribbean Sea was studied using records from oceanographic expeditions performed by the R/V Pillsbury. Sampled stations were sorted according to broad depth ranges and ecoregions and were analyzed in terms of species accumulation curves, variance in the species composition and contributions to alpha, beta and gamma diversity. According to the analysis of species accumulation curves using the Chao2 estimator, more diversity occurs on the continental slope (200–2000 m de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 56 publications
3
24
0
Order By: Relevance
“…Data were sorted according to major deep-sea zones and ecoregions. The major depth zones include: 1) the shelf, the mesophotic-aphotic realm, 60–200 m depth, close to coastal habitats, and relatively connected with shallow-water systems; 2) the slope, following the shelf, at 200–2000 m depth, aphotic, very close to the coast depending on their profile, and variable coastal influence; 3) the rise, open-sea stations, at 2000–4000 m depth, on the border of the Caribbean continental margin, includes the depth of the Aragonite saturation horizon in the Atlantic (approximately 2500 m deep [ 44 ]); 4) the abyssal, internal plains at Caribbean sub-basins, 4000–6000 m deep, and 5) the hadal (> 6000 m, restricted to the Puerto Rico trench)[ 31 , 45 ]. The biogeographical subdivisions follow Spalding et al [ 33 ] and includes 1) the Greater Antilles (59 Stations), 2) Eastern Caribbean (45 Stations), 3) Western Caribbean (21 Stations), 4) Southern Caribbean (53 Stations), 5) Southwestern Caribbean (79 Stations) and 6) the Guianian Ecoregion (21 Stations).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were sorted according to major deep-sea zones and ecoregions. The major depth zones include: 1) the shelf, the mesophotic-aphotic realm, 60–200 m depth, close to coastal habitats, and relatively connected with shallow-water systems; 2) the slope, following the shelf, at 200–2000 m depth, aphotic, very close to the coast depending on their profile, and variable coastal influence; 3) the rise, open-sea stations, at 2000–4000 m depth, on the border of the Caribbean continental margin, includes the depth of the Aragonite saturation horizon in the Atlantic (approximately 2500 m deep [ 44 ]); 4) the abyssal, internal plains at Caribbean sub-basins, 4000–6000 m deep, and 5) the hadal (> 6000 m, restricted to the Puerto Rico trench)[ 31 , 45 ]. The biogeographical subdivisions follow Spalding et al [ 33 ] and includes 1) the Greater Antilles (59 Stations), 2) Eastern Caribbean (45 Stations), 3) Western Caribbean (21 Stations), 4) Southern Caribbean (53 Stations), 5) Southwestern Caribbean (79 Stations) and 6) the Guianian Ecoregion (21 Stations).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence of diversity patterns as a function of depth, including clues in the Caribbean Basin, are based on the estimation of species ranges [ 3 , 29 ], which could generate a spurious unimodal model [ 30 ]. For the Caribbean Basin, sample-based estimations of diversity applied to deep-water corals have revealed more diversity at the continental slope than on the shelf [ 31 ] but species richness in deeper habitats is uncertain. The changes in diversity with depth could also be caused by turnover in species composition, species loss promoted by ecological filters associated with depth, or a combination of both processes [ 25 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three sites with deep-water corals between 70 m and 150 m depth identified in the Colombian Caribbean [6]; other corals were found corals in the same area at between 120 m and 180 m depth [15]. Deeper surveys have also been carried out, analyzing 210 stations in 8 sectors of the Colombian Caribbean between 10 m and 510 m deep, finding a diversity of deep-water corals [16], and deep-water corals were also studied in the Greater Caribbean area with more than 204 stations and a depth range between 60 and 5400 m depth [17]; their stations with deep water corals in the south Caribbean, most representative species were present no deeper than 480 m. The baseline studies performed on Gran Fuerte as a requirement for the environmental licenses showed no presence of deep-water corals in any of the box corer samples in the Gran Fuerte area as well [18]. However, the analysis of the 2006 survey did show two shallow (400 -800 m) ridges of hard substrate that is relatively near to a priority conservation site where deep-water corals were already reported (Figure 9).…”
Section: Cold Seep Activity Indications From Backscattermentioning
confidence: 99%
“…These field surveys resulted in the recognition of a deep-water coral structure called San Bernardo Bank (Lutz and Ginsburg, 2007), as well as others coral-dominated habitats (see Reyes et al, 2005, Santodomingo et al, 2007, Santodomingo et al, 2013 in the Caribbean continental shelf of Colombia. Then, we used a dataset on the benthic macrofauna from the R/V Pillsbury sampling program (1966 to 1972), including corals, mollusks and echinoderms, assembled from databases of the Natural Museum of Natural History, Smithsonian Institution and the Marine Invertebrate Museum, Rosenstiel School of Marine and Atmospheric Science (MIN-RSMAS) (Hernández-Ávila, 2014). Brachiopod data from the R/V Pillsbury sampling program were gathered from an extensive monograph on modern Caribbean brachiopods elaborated by Cooper (1977).…”
Section: Introductionmentioning
confidence: 99%